Pengetahuan Kewirausahaan di Bidang Pariwisata - Sofiani, Sofiani; Febriany, Kim (Universitas Bunda Mulia, 2023)
Entrepreneurial activities are increasing well in various countries including Indonesia. Business activities can play a role in increasing income, but also in various business structures in society. Entrepreneurship can also be the development of an interest in creativity and the courage to take risks for the work done in order to achieve the best results. Activities can be carried out properly by changing the pattern of exposure, namely by doing a more in-depth explanation. This community service activity is aimed at high school students and female students. It is hoped that by holding this activity it will be able to increase the interest of students in applying the entrepreneurship knowledge they got at school. The activity is carried out through online media zoom but still does not reduce the quality of the presentation where the presentation of introductory material about entrepreneurship in the tourism sector is made as active as possible by starting with an explanation about entrepreneurship and then continuing by giving several examples of entrepreneurial activities in the tourism sector to make it easier for students to get material. Based on the calculation of the average results of the feedback given as many as 40 students in the Educative category of 77% (Good) from this category it is hoped that the educativeness of the students can increase, and in terms of Objective it is 78% (Good) where is in accordance with what is expected, in terms of Accountability by 78% (Good), Transparent by 76% (Good).